Implementation of On Job Training (OJT) through Cooperation with the World of the Industry in Balai Latihan Kerja Padang - Nabilla Fitri; Jamaris Jamna (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the success of Balai Latihan Kerja (BLK) Padang as a place that creates competent workforce through the implementation of On Job Training. The purpose of this study is to see an implementation of On job Training in Balai Latihan Kerja (BLK) Padang. Thisresearch is quantitative descriptive reseaech. The population of this studyare 16 participants and the writer use census method to get the data. Thetools that being use in this research is a questionnaire sheets contains a list of statements.The data is analyze by using percentage formulas. The results of this study indicate that the implementation of On Job Training in terms of the stages of preparation, work practices, monitoring and evaluation are running well. The writer suggestions to this research are expected that participants can be involved in On Job Training preparation to support their implementation at working practices and also expected to provide assistance to participants in order to improve their competence in a real work and also it is hoped participants and organizers will do an evaluation to achieve On Job Training goals.Keywords: Training, Balai Latihan Kerja, On Job Training